2022
DOI: 10.1021/acs.oprd.2c00322
|View full text |Cite
|
Sign up to set email alerts
|

Flow Photo-On-Demand Phosgenation Reactions with Chloroform

Abstract: Oxidative photochemical conversion of CHCl3 to COCl2 occurred efficiently in the gas phase with a designed flow photoreaction system. Gram-scale phosgenation reactions for synthesizing chloroformates and carbonate esters, including polycarbonates, were facilitated with the semibatch and continuous flow reaction systems. Taking advantage of this photochemical reaction, which proceeds almost quantitatively in a short time without chemical reagents, catalysts, or solvents, we successfully demonstrated solvent-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…These results indicated that the photochemical oxidation of CHCl 3 occurred not only in the liquid phase but also in the gas phase. In support of this hypothesis, we recently reported that gaseous CHCl 3 underwent efficient photochemical oxidation to give COCl 2 in >96% yield . We expected that the photochemical oxidation of CHCl 3 would occur in the gas phase even with a heterogeneous mixture of CHCl 3 and water, given the large difference in their vapor pressures (21.1 and 2.3 kPa, respectively, at 20 °C) .…”
Section: Introductionmentioning
confidence: 75%
“…These results indicated that the photochemical oxidation of CHCl 3 occurred not only in the liquid phase but also in the gas phase. In support of this hypothesis, we recently reported that gaseous CHCl 3 underwent efficient photochemical oxidation to give COCl 2 in >96% yield . We expected that the photochemical oxidation of CHCl 3 would occur in the gas phase even with a heterogeneous mixture of CHCl 3 and water, given the large difference in their vapor pressures (21.1 and 2.3 kPa, respectively, at 20 °C) .…”
Section: Introductionmentioning
confidence: 75%
“…However, interestingly, 2,2,2-trifluoroethanol (TFE) allowed the reaction under the same conditions to give the corresponding TCAE and carbonate esters in 65 and 24% yields (entry 2), which likely originated from the reactions with TCAC and COCl 2 , respectively. TFE, having higher acidity (p K a = 12.4) than that of MeOH, may form an acid–base complex with pyridine to reduce its vaporization by increasing the nucleophilicity, causing the condensation reactions. The reaction was accelerated upon increasing the reaction temperature, increasing the yield of the carbonate ester (entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…The photochemical reactions of TCE with UV-C light were performed with reaction systems similar to those of the photo-on-demand in situ syntheses with CHCl 3 reported previously. , A low-pressure mercury lamp (LPML) mainly generates 184.9 and 253.7 nm light, which covers the electronic absorption bands of chlorinated alkanes originating from the σ–σ* and/or n –σ* transitions . The 20 W LPML (ø24 mm × 120 mm, illuminance at 5 mm distance: 2.00–2.33 and 5.96–8.09 mW/cm 2 at 185 and 254 nm, respectively) was inserted into the reaction system via a quartz glass jacket (ø28 mm × 150 mm) fixed in the center of a three-necked round-bottom flask (1 L) (Figure A) or a cylindrical flask (ø42 mm × 170 mm) as reported previously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, C-H hydrogen abstraction by Cl and subsequent oxygenation proceed under appropriate reaction conditions. Tsuda et al previously reported the synthesis of carbonates, [90][91][92] chloroformates, 93 Vilsmeier reagents, 94 urea and isocyanate (Scheme 19) by the in situ generation of COCl 2 via the oxygenation of CHCl 3 initiated by Cl under UV-light irradiation. 95 More recently, they have also reported CHCl 3 oxygenation under visible-light irradiation using trace amounts of Cl 2 as an initiator.…”
mentioning
confidence: 99%